1. а) (-10;-1), б) (0;-5,5), в) (-2;1)
2. а) (-1;5), б) (-3;1)
Объяснение:
1. C(x0;y0) - середина; х0=(х1+х2)/2; у0=(у1+у2)/2 (*)
а) х0=(-12-8)/2=-10; у0=(-3+1)=-1; С(-10;-1)
б) х0=(4-4)/2=0; у0=(-11+0)/2=-5,5; С(0;-5,5)
в) х0=(-2-2)/2=-2; у0=(9-7)/2=1; С(-2;1)
2. Из равенств (*) х1=2х0-х2 или х2=2х0-х1; у1=2у0-у2 или у2=2у0-у1
а) В(х2;у2); х2=0,5×2-2=-1; у2=1×2+3=5; В(-1;5)
б) А(х1;у1); х1=0×2-3=-3; х2=-1×2+3=1; А(-3;1)
1. а) (-10;-1), б) (0;-5,5), в) (-2;1)
2. а) (-1;5), б) (-3;1)
Объяснение:
1. C(x0;y0) - середина; х0=(х1+х2)/2; у0=(у1+у2)/2 (*)
а) х0=(-12-8)/2=-10; у0=(-3+1)=-1; С(-10;-1)
б) х0=(4-4)/2=0; у0=(-11+0)/2=-5,5; С(0;-5,5)
в) х0=(-2-2)/2=-2; у0=(9-7)/2=1; С(-2;1)
2. Из равенств (*) х1=2х0-х2 или х2=2х0-х1; у1=2у0-у2 или у2=2у0-у1
а) В(х2;у2); х2=0,5×2-2=-1; у2=1×2+3=5; В(-1;5)
б) А(х1;у1); х1=0×2-3=-3; х2=-1×2+3=1; А(-3;1)